Cut from a different cloth: Employee relations, job design and control of the labour process in Nordic-owned garment factories in the Baltic States. (1st April 2010) - Markku Sippola
Abstract : This paper focuses on labour market segmentation between the Nordic and Baltic parts of the production process. The Baltic segment of the Nordic clothing firms' value chain is examined through an analysis of employee relations, work design and control over the labour process. Although the Nordic mode of the labour process is not analysed in this study, it is regarded as mirroring the general features of the 'Nordic regime' with high wages, decent working conditions and a relatively high degree of worker autonomy and control over the labour process. The study draws on interview data gained from three small or medium-sized garment factories, located in post-Soviet Baltic States (Estonia, Latvia and Lithuania). The headquarters of these three subsidiary firms are located in Denmark, Norway and Sweden. The findings imply that the labour process in the Baltic garment industry has been easily 'locked in' to a downgraded position — both relatively, compared to that of Nordic countries, and absolutely, in real terms. This suggests that Nordic manufacturers opt for a 'low road' to investment and labour management in the Baltic subsidiaries even whilst following a 'high road' path at home.